Fetal and neonatal exposure to nicotine results in increased adiposity: role of the gut microbiome - VanDuzer, Taylor A (My University, 2015)
Introduction: Maternal smoking is a risk factor for childhood overweight and obesity. However, the mechanisms underlying this association are largely unknown. Smoking is associated with changes in the composition of the maternal microbiome and there is now considerable evidence to suggest that the infant microbiome may play an important role in the development of obesity. Therefore we hypothesized that fetal and neonatal exposure to nicotine, the major addictive component of cigarettes, would result in dysbiosis, an alteration in the composition of the microbiome, in postnatal life. Methods: Nulliparous female Wistar rats were randomized to receive daily injections of saline (N=20) or nicotine bitartate (1.0 mg/kg/d; N=20) from 2 weeks prior to mating until weaning. We assessed markers of inflammation, gut permeability, and the composition of the gut microbiota in the offspring. Results: At the phyla level, exposure to nicotine resulted in alterations in the proportion of both Firmicutes and Bacteriodetes at 26 weeks of age. There were significant changes in a number of operational taxonomic units (OTUs) at 3, 12 and 26 weeks of age. Of note, a number of OTUs for Firmicute Clostridia Clostridiales Lachnospiraceae and Firmicute Clostridia Clostridiales Ruminococcus were decreased in the nicotine-exposed offspring which may suggest increased energy extraction in these animals. Although there was evidence of altered gene expression in pathways regulating inflammation and development, these did not result in increased inflammation or aberrant gut development Conclusion: Maternal nicotine-exposure resulted in dysbiosis in the gut of the offspring; an effect that persisted into adulthood. Since dysbiosis has been associated with increased weight gain and adiposity, these data suggest that alterations in the gut microbiome as a result of maternal nicotine-exposure may explain, in part, the increased risk of obesity in children born to mothers who smoke.
Keywords: Microbiome; Nicotine; pregnancy